Determinants of Governance Performance: The Effects of Intellectual, Social, and Natural Capital in Middle-Income Countries - Thahira, Zia; Dawood, Taufiq C.; Zikra, Naswatun; Darmawati, Cut (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2025)
Objective: This study investigates the effect of intellectual, social, and natural capital on governance performance in middle income countries, addressing how non-financial resources shape institutional quality. The research is empirical and contributes to development economics by linking capital endowments with governance outcomes, which are central to sustainable development and institutional resilience. Methods: The study uses panel data from the Global Sustainable Competitiveness Index (GSCI) for 20 middle income countries during 2020–2024. Governance scores serve as the dependent variable, while intellectual, social, and natural capital are the main explanatory variables, analyzed through a fixed effects regression with robust standard errors. Findings: The results indicate that natural capital has a statistically significant and positive impact on governance performance, with a coefficient value of approximately 0.51, significant at the five percent level. This suggests that countries with stronger capacities to manage environmental resources tend to develop more accountable and resilient institutions. In contrast, intellectual and social capital do not show significant effects within the observed period, which may imply that their influence on governance is more indirect, requires longer time horizons to materialize, or depends on the presence of supportive institutional frameworks. Originality/Value: The novelty of this study lies in testing the reverse relationship between non-financial capital and governance and incorporating interaction models that reveal how these resources jointly shape institutional outcomes. Unlike most prior studies that focus on how governance drives capital formation, this research centers on middle-income countries and employs recent data from 2020–2024 to offer fresh empirical evidence on institutional determinants of governance. Practical/Policy implication: The findings suggest that governance reforms should integrate natural capital management within Sustainable Development Goal frameworks while enhancing institutional capacity in education and social cohesion to enable intellectual and social capital to more effectively strengthen governance in the long term.